Keeping it Clean: A Healthy House - Mary N. Harrison (EDIS)
The way you keep your home will affect the health of your family and especially of your children. The number of children with asthma is increasing. You can help make your home a safe and healthy place for your children by eliminating or controlling the risks outlined in this publication. This document is FCS5232-01, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. Original publication date June 2002. Revised December 2006.